Analysis of Saliva Composition: Parathyroid Hormone-Related Protein, Total Protein, and Secretory Immunoglobulin A (sIgA) in Rattus norvegicus with Stunted Growth - Tedjosasongko, Udijanto; Nelwan, Sindy Cornelia; Wahluyo, Soegeng; Puteri, Mega Moeharyono; Dewi, Ardianti Maartrina; Rahayu, Retno Pudji; Ardiwirastuti, Ilvana; Ayuningtyas, Puspita; Pramudita, Regina Ayu; Marwah, Aisyah (European Journal of Dentistry, 2022)
Objective This study aimed to determine total protein, secretory immunoglobulin A (sIgA) and parathyroid hormone-related protein (PTHrP) levels in the saliva of rats with stunted growth.Materials and Methods Experimental laboratory research with a pre-and posttest control group design was conducted. Seventeen albino rats (Rattus norvegicus) were divided into the control group (eight rats) and the treatment group (nine rats). Rats in the treatment group were exposed to aflatoxin B1 5µg/kg orally for 5 weeks. Anthropometry data (body length, body weight) and saliva of R. norvegicus were collected. The levels of PTHrP and sIgA in the saliva were measured using an enzyme-linked immunosorbent assay kit for rats and the Bradford test for total protein and analyzed using SPSS 25.0.Results Aflatoxin caused stunted growth in rats in the treatment group. There was a significant difference in body length, salivary flow, PTHrP, sIgA, and total protein in the treatment group compared with the control group. The average rat's body length change in the control group was 6.4 ± 1.1mm/5 weeks, while in the treatment group, the change was 3.7 ± 0.9 mm /5 weeks. There was no significant weight gain in the treatment group compared with the normal group. The average values of PTHrP, sIgA, and total protein in the control group were x̄0.9, x̄18, and x̄0.7 m./L, respectively, while in the treatment group, they measured x̄0.4, x̄10.7, and x̄0.5 mg/L, respectively.Conclusion This study showed that salivary flow, PTHrP, sIgA, and total protein levels in the saliva were significantly lower in stunted rats compared with normal rats.
Keywords: stunting; PTHrP; sIgA; total protein